High intraguild predator density induces thinning effects on and increases temporal overlap with prey populations. Issue 2 (26th November 2013) - Anderson, Thomas L.; Semlitsch, Raymond D.
Abstract: Intraguild (IG) predator density can alter its effects on intraguild prey populations through several mechanisms, including density‐dependent processes that affect IG predator traits such as size or growth that enhance or limit its predatory abilities. We examined whether intraspecific density‐dependence altered IG predator traits, as well as the subsequent interspecific effects among its intraguild prey within a larval salamander guild. Four densities of ringed salamanders ( Ambystoma annulatum ), the IG predator, were combined with the presence/absence of spotted salamanders ( A. maculatum ), the IG prey, within experimental mesocosms. We modeled the effects of A. annulatum density on both conspecific and heterospecific responses that would be indicative of density‐dependent competition and predation, respectively. We also modeled the reciprocal interspecific effects of A. maculatum on A. annulatum . We found that increasing intraspecific density negatively affected morphological traits but not survival of A. annulatum . No interspecific effects of A. maculatum on A. annulatum were observed. Alternatively, traits of A. maculatum showed nonlinear relationships with increasing A. annulatum density. Thinning effects of A. annulatum on A. maculatum were observed, as survival was positively and size negatively related for A. maculatum with IG predator density. The temporal overlap of the IG predator and prey also increased nonlinearly with IG predator density, intensifying the potential encounter rate of the two species. Overall, this study shows that density‐dependent processes in IG predators can significantly affect traits of both themselves, as well as IG prey, which could ultimately change whether competition or predation occurs between the two groups.